O desenho de meninas e meninos na educação infantil: um estudo sobre relações de gênero na infância - Silva, Daniele Duarte [UNIFESP] (2016)
This master?s research was done with 4 and 5-year-olds in a children early education institution in municipal schools of the city of Sao Paulo. The purpose is to examine the drawings made by girls and boys and listen to what they tell us about gender representation. This work presents the challenges of what it means to be both a teacher of and a researcher of little children. It also investigates children?s drawings as possibilities of communication, interaction, and expression, seeking to identify issues that the drawings have revealed to us about gender marks brought in by children, marks that are connected to the construction of female and male identities. The research looks for the presence of gender as it is expressed in the cultural symbols that are found in the drawings, traces, colors, topics, and themes represented by children in their creations. It has as theoretical framework the studies about children?s drawings, contributions in the field of childhood sociology, and childhood gender studies. Methodological procedures for this research seek the children?s perspective connecting drawings to orality, and taking into consideration the experiences narrated and interpreted by boys and girls in their drawings. The results show that boys and girls are able to ?speak? about the gender relations as well as other topics that are present in their day-to-day. They also show that their drawings have marks of the permanence of gender stereotypes as well as the ruptures with gender inequalities. The drawings of boys and girls and their talks show us the meanings children build regarding what it means to be a man and a woman, which are the places and situations reserved for them and which of them are being created in the gender relations that they experience daily. The children?s drawings are brought in as social representations, fruit of their social and cultural experiences; they allow us to understand a little more about their culture and childhood.